KARAKTERISTIK KOLEKSI SPESIMEN TIPE BAMBU DI HERBARIUM BOGORIENSE, PUSAT PENELITIAN BIOLOGI – LIPI - Putu Gede P. Damayanto, I; Rahmawati, Kusuma (BACA: Jurnal Dokumentasi dan Informasi, 2018)
The aim of this study is to explore information about the characteristics of collections of the type specimens of bamboo in Herbarium Bogoriense (BO) to obtain the infografic status of the collections. The study was conducted in April-May 2018 at BO, Research Center for Biology ‒ LIPI with direct observation method. The population, as well as the sample of the research, is the whole collections of type specimens of bamboo in BO. Data obtained by examining and recording the entire collection of type specimens of bamboo in BO. Characteristics that observed are species names, collectors, number and year of collection, discovery location, number of sheets, specimen conditions, the journal of publication and year, kind of type and duplicate location. Each of species name is validated before it is analyzed. The data were analyzed and presented qualitatively as the tables and charts. There are 107 species from 117 collection numbers of type specimens of bamboo in BO. Two numbers collection from two species is not found. The most type specimen is from Gigantochloa (20,5%). Approximately 63,5% of type specimens were published and/or proposed the combinations of names by LIPI researchers. Elizabeth A.Widjaja is the collector of the most type specimens (43,6%). The highest period (34,2%) of collection activities was in 1991-2000. About 62,6% of type specimens are collected from various islands in Indonesia. There are 577 sheets of type specimens in BO, 92% are in good condition and 8% is good enough. There are 51,3% of holotype specimens in BO, followed by isotype (30,8%), paratype (11,1%), lectotype (2,6%), neotype (2,6%), epitype (0,8%), and isosyntype (0,8%). As many as 50% holotypes has duplicates in more than two different of herbarium locations, the other 37% are without duplicates. About 56% of type specimens are published in the journal of Reinwardtia and 16,8% in Kew Bulletin.